Effectiveness and Tolerability of Repeated Courses of Viscosupplementation in Symptomatic Hip Osteoarthritis: A Retrospective Observational Cohort Study of High Molecular Weight vs. Medium Molecular Weight Hyaluronic Acid vs. No Viscosupplementation - De Lucia, Orazio; Pierannunzii, Luca Massimo; Pregnolato, Francesca; Verduci, Elisa; Crotti, Chiara; Valcamonica, Elisabetta; Pisoni, Laura; Comi, Daniela; Lonati, Paola Adele; Meroni, Pier Luigi; Murgo, Antonella (Frontiers in Pharmacology, 2019)
Background: Nonsurgical management of symptomatic hip osteoarthritis needs real-world evidence. We evaluated the effectiveness and tolerability of US-guided intra-articular treatment of two hyaluronic acids (HAs) commercially available in Italy and investigated predictors of response. Methods: Outpatient records including three cohorts: 122 subjects treated with medium (1,500–3,200 kDa; Hyalubrix®) molecular weight (MW) or high (hylan G-F20; Synvisc®) MW HAs and 20 controls taking NSAIDs/analgesics on demand were retrospectively analyzed. Pain VAS score, WOMAC, NSAID/analgesic consumption, and causes of suspension were available at 1, 6, 12, and 24 months after first administration. As selection bias usually affects observational retrospective studies, a quasi-randomization process was attained by performing propensity score approach. Results: Propensity score adjustment successfully allowed comparisons among balanced groups of treatments. VAS and WOMAC considerably decreased over time in treated groups independently of the radiological grade (p<0.001). On the other hand, the control group showed only a slight and rather uneven variation in VAS. Mean score changes were comparable in both HA cohorts from the earliest stages (ΔVAS(HA1,500–3,200kDa)T1vsT0 = −20%; ΔVAS(hylan G-F20)T1vsT0 = −23%/ΔWOMAC(HA1,500–3,200kDa)T1vsT0 = −17%; ΔWOMAC(hylan G-F20)T1vsT0 = −19%), reaching a further substantial reduction after 12 months (ΔVAS(HA1,500–3,200kDa)T12vsT0 = −52%; ΔVAS(hylan G-F20)T12vsT0 = −53%/ΔWOMAC(HA1,500–3,200kDa)T12vsT0 = −45%; and ΔWOMAC(hylan G-F20)T12vsT0 = −47%). Almost 11% (=13/122) of ineffectiveness and few moderate local side effects 3% (=4/122) were detected. Conclusions: Viscosupplementation in a real-life setting seems to provide a sound alternative in pain management in comparison to oral NSAIDs/analgesics, guaranteeing a reduced intake of pain killer medications. Analgesic effectiveness, functional recovery, and reduced joint stiffness extend and improve over 12 and 24 months, suggesting that repeated administrations achieve an additive effect.